2014
DOI: 10.1007/s10561-014-9458-5
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of soybean lecithin-based semen extender by antioxidants: complementary flowcytometric study on post-thawed ram spermatozoa

Abstract: The purpose of the current study was to evaluate the effects of cysteine (C) and glutathione (G) on the post-thawed ram sperm quality. Collected semen samples from four mature rams were diluted with five soybean lecithin (SL)-based extenders containing: no antioxidant (SL-0), 5 mM cysteine (SL-C5), 10 mM cysteine (SL-C10), 5 mM glutathione (SL-G5) and 10 mM glutathione (SL-G10). After freeze-thawing process, motion and velocity parameters, plasma membrane integrity and functionality, morphological abnormality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…These data indicate that cysteine protects rabbit spermatozoa from damage during cooling, freeze-thawing, and post-thaw incubation. In the previous studies, addition of cysteine to freezing extender increased the motility and membrane integrity of the frozen-thawed spermatozoa in cats [20], buffalos [14], goats [18, 19], rams [21], and boars [9]. Furthermore, addition of cysteine significantly decreased the level of 8-OHdG, which is a biomarker for DNA oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that cysteine protects rabbit spermatozoa from damage during cooling, freeze-thawing, and post-thaw incubation. In the previous studies, addition of cysteine to freezing extender increased the motility and membrane integrity of the frozen-thawed spermatozoa in cats [20], buffalos [14], goats [18, 19], rams [21], and boars [9]. Furthermore, addition of cysteine significantly decreased the level of 8-OHdG, which is a biomarker for DNA oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Uysal and Bucak (2007) [7] reported that cysteine enhanced intracellular glutathione (GSH) biosynthesis and protected the proteins, DNA and membrane lipids because of the direct radical-scavenging ability of GSH. It has been shown that cysteine protects spermatozoa against cryo-damage in boars [8, 9], bulls [10, 11], buffalos [12–14], dogs [15], chickens [16], goats [1719], cats [20], and rams [6, 7, 21, 22]. However, the underline mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, possible problems of egg yolk such as bacterial contamination and quality variation have been reported [8,17]. Therefore, it seems that replacement of egg yolk by an alternative cryoprotectant has several advantages, such as improvement of consistency in the semen extenders components, hygienic risks elimination and improvement of fertility after freeze-thawing [31].…”
Section: Discussionmentioning
confidence: 99%
“…Soybean lecithin (SL) has recently been successfully applied as an extracellular cryoprotectant for cryopreservation of semen in ram [11,30], goat [27], bull [1], buffalo [2] and human [23]. In recent years, SL has been a replacement for egg yolk (EY) due to increment the risk of microbial contamination of egg yolk base extenders [31]. In addition, EY increases the agglutination and pre-capacitation of sperm that has crucially effects on sperm quality [9,16].…”
Section: Introductionmentioning
confidence: 99%
“…Low-molecular weight amino acids were widely used as additives in ram semen extenders. Among them methionine, cysteamine and cysteine were extensively studied and were indicated as supplements that can reduce malondialdehyde's levels and improve post-thaw ram semen parameters Najafi et al, 2014;Sharafi et al, 2015;Toker et al, 2016). However, there are relative to the aforementioned amino acids studies, which report negative effects of cysteamine on semen motility, mitochondrial activity and DNA integrity (Cirit et al, 2013; Mata-Campuzano et al,…”
Section: Ii) Non-enzymatic Antioxidantsmentioning
confidence: 99%